Sex and gender differences in the treatment of Alzheimer's disease: A systematic review of randomized controlled trials. (January 2017) - Canevelli, Marco; Quarata, Federica; Remiddi, Francesca; Lucchini, Flaminia; Lacorte, Eleonora; Vanacore, Nicola; Bruno, Giuseppe; Cesari, Matteo
Graphical abstract: Abstract: In recent years, epidemiological, clinical, and biological evidence has drawn the attention on the influence of sex and gender on Alzheimer's disease (AD). Nevertheless, not enough attention has been paid to their impact on treatment outcomes. The present study is aimed at systematically retrieve, review and discuss data coming from available randomized placebo-controlled trials (RCTs) on currently marketed treatments for AD (i.e., cholinesterase inhibitors [ChEIs] and memantine) in order to describe possible sex and gender differences in their efficacy, safety and tolerability. A systematic review of literature was performed. None of the retrieved studies reported data on the efficacy, safety and tolerability of considered medications separately in male and female patients with AD. We thus analyzed 48 excluded studies of potential interest, that is, almost all of the currently available trials on the four considered drugs. Nearly all the considered RCTs recruited a larger number of female participants to mirror the sexually unbalanced prevalence of AD. Only two studies took into account the potential influence of sex and gender on treatment efficacy, reporting no significant differences between men and women. None of the studies investigated potential sex and gender differences in the safety and tolerability of the four considered treatments. The existence of sex and gender differences in the efficacy and tolerability of ChEIs and memantine in AD has, to date, drawn limited to no attention. However, a considerable amount of data, with an adequate representativeness in terms of sex/gender distribution, seem to be already available for dedicated analyses on this topic. A greater effort should be made to collect and report data on those factors interacting with sex and gender that may significantly influence clinical manifestations, outcomes, and trajectories over time of AD patients.